Spectral Characteristics of Seagrass with Landsat TM in Northern Sabah Coastline, Malaysia - Hashim, Mazlan (Asian Association on Remote Sesning, 2001)
The spectral characteristics of Landsat TM bands 1, 2 and 3 were examined over identified seagrass area in the South China Sea, off northern coastline of Kota Kinabalu, Sabah, Malaysia. Two seagrass types namely the low and high dense classes were used in this study. Two main extraction techniques employed ere the spectral transform based on band ratioing and radiative transfer model. Results of this study indicated that band ratio of band 2/band 1 gave a better spectral response to high dense and low dense seagrass distribution than band 3/band1, whereas band ratioing after applying radiative transfer model could not detect any seagrass in the study area.